Pengaruh Sistem Pembayaran Berbasis QRIS dan Pelayanan Terhadap Keputusan Transaksi Konsumen: Studi Kasus Warung Rasbani Selong Lombok Timur - Zahratun Maulidiati; Muh. Rabbul Jalil; Muh. Khairul Fatihin (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the effect of QRIS-based payment systems and service quality on consumer transaction decisions at Warung Rasbani, Selong, East Lombok. The study applies the Technology Acceptance Model (TAM) to understand the adoption of digital payment technology, the Servqual theory to assess service quality, and the transaction decision concept in consumer behavior. The research type is associative with a quantitative approach, aimed at identifying cause-and-effect relationships between independent and dependent variables. Data were collected through direct observation, documentation, and questionnaires distributed to Warung Rasbani consumers. Data analysis was performed using multiple linear regression with t-tests for partial hypotheses and F-tests for simultaneous hypotheses. The results indicate that QRIS-based payment systems (X1) and service quality (X2) partially have a significant effect on consumer transaction decisions (Y), with t_calculated for QRIS = 2.980 > t_table = 2.056, and for service = 3.817 > 2.056. Simultaneously, both variables significantly influence transaction decisions with F_calculated = 13.988 > F_table = 2.98. The coefficient of determination (R²) is 50.9%, indicating that 50.9% of transaction decisions are influenced by QRIS and service quality. This study provides practical implications for MSMEs to optimize digital payment technology and enhance service quality to improve consumer satisfaction and loyalty.